Enhanced determination of Streptococcus pneumoniae serotypes associated with invasive disease in Laos by using a real-time polymerase chain reaction serotyping assay with cerebrospinal fluid. - Moore, C; Sengduangphachanh, A; Thaojaikong, T; Sirisouk, J; Foster, D; Phetsouvanh, R; McGee, L; Crook, D; Newton, P; Peacock, S (2010)
A prospective hospital-based study was undertaken to define the incidence of invasive pneumococcal disease (IPD) and circulating serotypes in Laos. Of 10,799 patients with hemocultures and 353 patients with cerebrospinal fluid samples, 0.21% and 5.4%, respectively, were positive for Streptococcus pneumoniae, giving a total of 35 IPD patients. We developed a real-time polymerase chain reaction to detect serotypes represented in the 13-valent pneumococcal vaccine. A blinded evaluation comparing serotype as defined by the Quellung reaction versus the polymerase chain reaction demonstrated 100% concordance. The most frequent serotype (n = 33 patients) was 1 (n = 6), followed by serotypes 5, 6A/B/C, 14, and 23F. Serotypes represented in the 7-valent polysaccharide-protein conjugate vaccine (PCV-7) infected 39% of patients, with 73% coverage for the PCV-10 and PCV-13 vaccines. Although the sample size is small, these data suggest that the PCV-7 vaccine may have relatively low efficacy in Laos. Further studies are urgently needed to guide pneumococcal vaccine policy in Laos.